Internet kiosks in rural India: What influences success? - Jake Kendall; Nirvikar Singh (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
In this paper we investigate an example of a very widely applied model for the delivery of IT services to rural and poor populations. The model is one where limited intervention to support infrastructure and coordinate resources is combined with marketbased delivery of IT services to the end user (what we call here the sustainable franchise model). Though this model has been deployed world-wide by governments, NGOs, and development institutions in the past few years, there has been little research into the determinants of success in such a model. In this paper we examine the example of n-Logue, a franchise of over 1000 locally-owned, Internet kiosks in rural villages in India. We seek to assess how this new sustainable franchise model has worked in practice by analyzing data from 74 of n-Logue's kiosks. Among other things, we find that gender and education do not affect success, while location and other measures of social standing (age and caste) do. We also find that the uses that villagers have for IT services are not so different from those which first world users have. The lessons we draw from this example are that while local customs and practices must be taken into account (e.g. the caste system), it is not a foregone conclusion that social biases (e.g. against women) cannot be mitigated by good program design.
Keywords: 330; Internet; Informationstechnik; IT-Dienstleister; Franchising; Ländlicher Raum; Indien